Profil Kondisi Fisik Pemain Futsal Klub Brancos Kota Lubuklinggau - M Syroyyudin; Rais Firlando; Ever Sovensi (Silampari Jurnal Olahraga, 2021)
This study aims to determine the level of physical condition of futsal players at the Brancos Club, Lubuklinggau City. The method used is a survey. The sample is 20 people with the sampling technique using total sampling. Data collection in this study used 5 physical condition test items, namely (1) 6-second Sprint test for speed, (2) Illinois Agility Run test, (3) standing long jump test, (4) bleep test, (5) sit-up test. 60 seconds. The results of data analysis for the speed test (sprint) with an average value = "2" can be categorized as "less", the agility test (Illinois agility run test) with an average value = "3" can be categorized as "enough", on the test leg power (standing long jump) with an average value = "2" can be categorized as "less", on the heart and lung endurance test (bleep test) with an average value = "2" it can be categorized as "less", and Abdominal muscle endurance test (sit ups) with an average value = "3" can be categorized as "enough". Overall it can be concluded that the profile of the physical condition of the Brancos club futsal players is in the "Medium" category